Memahami Penerimaan Diri pada Pengidap HIV Melalui Talkshow - Dewi, Lharasati; Indriani, Dewi; Kumala Dewi, Dinda; Puji Lestari, Marsela; Atussolihah, Mar; Saputra, Aditya (Universitas Methodist Indonesia, 2025)
The stigma and psychological burden experienced by people living with HIV/AIDS (PLWHA) often hinder their self-acceptance process. This community service activity aimed to support self-acceptance among young men living with HIV in Samarinda through an interactive talk show. The program involved 15 participants aged 18–25 years from the Mahakam Plus Community and featured two professional speakers who discussed gratitude strategies and the role of family support. Activities included material presentations, group discussions, relaxation exercises, and reflective practices such as gratitude journaling and a